Impact of fumaric acid esters on cardiovascular risk factors and depression in psoriasis: a prospective pilot study - Schmieder, Astrid; Poppe, Manuel; Hametner, Christian; Schaarschmidt, Marthe-Lisa; Findeisen, Peter; Goerdt, Sergij; Ludwig-Peitsch, Wiebke (Archives of dermatological research, 2015)
Patients with psoriasis have an increased risk of cardiovascular disease that is partly attributable to chronic systemic inflammation. The aim of our prospective pilot study was to investigate the impact of fumaric acid esters (FAE), a first-line systemic antipsoriatic treatment in Germany, on cardiovascular risk parameters. Participants with moderate-to-severe psoriasis from the University Medical Center Mannheim and the University Hospital Würzburg were treated with FAE for 16 weeks according to standard dosage recommendations. Disease severity, life quality and depression scores as well as biomarkers of inflammation, lipid and glucose metabolism were assessed prior to initiation of FAE and after 16 weeks. Out of 39 participants recruited, 27 completed the study. 44 % of all participants and 63 % of those completing the 16-week treatment achieved PASI 50 response and 27 or 37 % PASI 75 response. Clinical improvement was paralleled by significant improvement in quality of life, high treatment satisfaction and significant reduction of depressive symptoms. Adverse events, most frequently mild gastrointestinal complaints, flush and lymphocytopenia occurred in 89 %. FAE did not modify glucose metabolism or inflammatory parameters substantially. However, a highly significant increase in serum levels of the atheroprotective cytokine adiponectin was noted after 16 weeks (median 4.7 vs. 8.9 µg/ml; p = 0.0002). Our study demonstrates a significant beneficial impact of FAE on adiponectin, indicating a potential cardioprotective effect. It will be interesting to verify this finding in larger cohorts and to assess the long-term influence of FAE on cardiovascular risk and disease.